(untitled) (مجلة إحالات, 2026)
The modern poetic discourse aims to construct a distinctive aesthetics that sets it apart from the inherited classical poetic traditions, which have become entrenched as previous experiences in the history of Arab reception. Modern poetic writing diverges from the conventional by rushing to create new stylistic elements, intending to break the reader’s expectations and build a fresh interpretation of poetic texts. As a result, modern poets have opened the door to extensive poetic experimentation, seeking poetic characteristics that embody the temporal specificities to which they belong. This involves posing new questions related to the contemporary world and its psychological crises. The collection ’Halaj AlNihayat’ is one of the experiments that embarked on the adventure of this poetic experimentation, attempting to surpass prevailing norms and establish new perspectives on existence, humanity, and the world.